Financial Feasibility Analysis of Sweet Hami Melon Cultivation with DRFT Hydroponic System (Dynamic Root Floating Technique) (Case Study: Indogarden Greenhouse Tuban) - Harya, Gyska Indah; Khairani, Fahril Laili; Laksono, Heksa Budi; Naldi, Brian Pikto; Wikarsa, Ommar Galih (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2025)
This study aims to analyse the financial feasibility of the melon cultivation of the Sweet Hami variety with the DRFT (Dynamic Root Floating Technique) hydroponic system at Indogarden Greenhouse, Tuban. The research method employed is a descriptive quantitative approach, utilising primary data collected through interviews and secondary data sourced from the Indogarden Greenhouse Farm's business bookkeeping records for the period 2023–2025. The business feasibility analysis used the criteria of Net Present Value (NPV), Internal Rate of Return (IRR), Benefit-Cost Ratio (B/C), and Payback Period (PP). The results of the analysis showed that the premium melon cultivation business at Indogarden Greenhouse is feasible to develop. This is indicated by the NPV value of Rp72,869,633.98 (positive) at an interest rate of 6.5%, IRR of 29%, which is greater than the interest rate of 6.5%, B/C ratio of 1.7 (more than 1), and a payback period of 4 harvests. These financial indicators consistently show that investment in this premium melon farming business can provide significant profits and return on capital in a relatively short time, so it has high potential for sustainability. Contribution to Sustainable Development Goals (SDGs):SDG 2: Zero HungerSDG 8: Decent work and economic growthSDG 9 - Industry, Innovation, and InfrastructureSDG 12 – Responsible Consumption and Production